Flavonoids and other polyphenols - Packer, Lester (Academic Press, 2001)
The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Now with more than 300 volumes (all of them still in print), the series contains much material still relevant today-truly an essential publication for researchers in all fields of life sciences.This volume presents an extensive collection of new methodologies to aid progress in solving unanswered questions concerning the bioavailability and metabolism of flavonoids and polyphenols, their biochemical and molecular biological effects on cell regulation, and their effects on health. Major topics in this volume include sources, characterization, analytical methods, bioavailability, antioxidant action, and biological activity.
Methods in enzymology ; vol. 335
Keywords: enzymy; fenoly; Flavones; vnitřní lékařství; Phenols; flavony; Enzymes